Characterisation of Drosophila UbxCPTI000601 and hthCPTI000378 Protein Trap Lines - Siew Woh Choo; Ching Yew Beh; Steven Russell; Robert White (The Scientific World Journal)
In Drosophila, protein trap strategies provide powerful approaches for the generation of tagged proteins expressed under endogenous control. Here, we describe expression and functional analysis to evaluate new Ubx and hth protein trap lines generated by the Cambridge Protein Trap project. Both protein traps exhibit spatial and temporal expression patterns consistent with the reported endogenous pattern in the embryo. In imaginal discs, Ubx-YFP is expressed throughout the haltere and 3rd leg imaginal discs, while Hth-YFP is expressed in the proximal regions of haltere and wing discs but not in the pouch region. The UbxCPTI000601 line is semilethal as a homozygote. No T3/A1 to T2 transformations were observed in the embryonic cuticle or the developing midgut. The homozygous survivors, however, exhibit a weak haltere phenotype with a few wing-like marginal bristles on the haltere capitellum. Although hthCPTI000378 is completely lethal as a homozygote, the hthCPTI000378/hthC1 genotype is viable. Using a hth deletion (Df(3R)BSC479) we show that hthCPTI000378/Df(3R)BSC479 adults are phenotypically normal. No transformations were observed in hthCPTI000378, hthCPTI000378/hthC1, or hthCPTI000378/Df(3R)BSC479 embryonic cuticles. We have successfully characterised the Ubx-YFP and Hth-YFP protein trap lines demonstrating that the tagged proteins show appropriate expression patterns and produce at least partially functional proteins.